2020
DOI: 10.3928/01477447-20200107-03
|View full text |Cite
|
Sign up to set email alerts
|

Open Biceps Tenodesis: A Biomechanical Comparison of 6 Fixation Techniques

Abstract: Tenodesis is used to treat pathology of the long head of the biceps tendon. The authors evaluated the biomechanical properties of 6 techniques for biceps tenodesis fixation. The authors dissected 42 fresh-frozen cadaveric shoulders (mean age, 71±9.8 years; 69% male specimens), leaving the proximal humerus, proximal biceps tendon, and pectoralis major insertion. Specimens were randomized to undergo biceps tenodesis with one of the following: (1) an interference screw; (2) a cortical button; (3) a double-loaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…7 However, other studies have found equivalence in biomechanical performance of all-suture anchors and interference screws, 2,12 with some cadaveric studies suggesting that interference screw may even be inferior with load-to-failure testing. 4 While that may be the case, all cadaveric studies are implicitly time zero and do not allow for tissue remodeling, nor do they necessarily simulate what happens physiologically in vivo, where healing is primarily periosteal. 23,26 The authors of this study postulate that interference screws may be superior because they cause apposition of tendon tissue to cortical bone, which is superior to any suture construct in which suture material can pull through the longitudinally oriented fibers of the biceps tendon.…”
Section: Discussionmentioning
confidence: 99%
“…7 However, other studies have found equivalence in biomechanical performance of all-suture anchors and interference screws, 2,12 with some cadaveric studies suggesting that interference screw may even be inferior with load-to-failure testing. 4 While that may be the case, all cadaveric studies are implicitly time zero and do not allow for tissue remodeling, nor do they necessarily simulate what happens physiologically in vivo, where healing is primarily periosteal. 23,26 The authors of this study postulate that interference screws may be superior because they cause apposition of tendon tissue to cortical bone, which is superior to any suture construct in which suture material can pull through the longitudinally oriented fibers of the biceps tendon.…”
Section: Discussionmentioning
confidence: 99%
“…8 Various methods have been used to increase time-zero fixation strength. 9 However, the best methods are still being pursued. We believe that the described 2-position fixation method may shed some light on the treatment of LHB disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation devices for biceps tenodesis have been well studied, with multiple devices on the market. 1,6,7,11 However, it is unclear whether these affect clinical outcomes despite biomechanical differences. Dekker et al 5 performed a metaanalysis of biomechanical studies evaluating biceps tenodesis and found no difference in fixation type (interference screw vs. other tenodesis techniques) or location (suprapectoral vs. subpectoral).…”
Section: In Replymentioning
confidence: 99%